Riding Across Time and Space: A Case Study of the Political Uses of Medieval Images in Portugal During the Estado Novo. (2nd April 2016) - Miguélez Cavero, Alicia
Abstract : Over the course of the twentieth century, various political regimes in Europe used medieval images to demonstrate and legitimize their power. The present study takes as its focus the case of Portugal and, more precisely, an illumination in the twelfth-century Portuguese manuscript known as the Lorvão Beatus, a copy of the Commentary on the Apocalypse written in northern Spain in the eighth century and attributed to the monk Beatus of Liébana (c. 730–800). This manuscript's depiction of the Four Horsemen of the Apocalypse was frequently utilized during the first decades of the Estado Novo (New State), a dictatorship that ruled Portugal from 1933 to 1974. The Estado Novo was headed by António de Oliveira Salazar (1889–1970) until 1968, when Salazar retired due to ill health and was replaced by Marcelo Caetano (1906–1980), who ruled until 1974, the year of the Revolução dos Cravos (Carnation Revolution) which returned democracy to Portugal. The Estado Novo developed the so-called Política do Espírito (Politics of the Spirit), a cultural policy that attempted to reinvent Portuguese national identity in order to advance its own ideology. In conjunction with this effort, the artists who worked with the Secretariado de Propaganda Nacional (Department of National Propaganda) appropriated the depiction of the Four Horsemen in the Lorvão Beatus – either adopting it as a direct model or more loosely alluding to it – as a symbol of Portuguese identity. The example of the Lorvão Horsemen reveals how the Estado Novo used medieval images for propagandistic purposes, to help legitimize their rule and to assert their own place in Portuguese history.